+0

# 2° Functions, Delta

+5
345
3

ax^2 +bx +c has 2 solutions, x1 and x2  x1=(-b+√Δ)/2a and x2=(−b−√Δ)2a. Is it possible that x1 + x2 = x1/x2?

Guest Dec 13, 2015

#2
+18827
+10

ax^2 +bx +c has 2 solutions, x1 and x2  x1=(-b+√Δ)/2a and x2=(−b−√Δ)2a. Is it possible that x1 + x2 = x1/x2? YES

$$\small{ \begin{array}{lrcll} (1) & x_1+x_2 &=& k & \qquad \rightarrow \qquad x_2 = k-x_1\\ (2) & \frac{x_1}{x_2} &=& k & \qquad \rightarrow \qquad x_1 = k \cdot x_2 \qquad \rightarrow \qquad x_1 = k \cdot (k-x_1)\\ \\ \hline \\ (2) & x_1 &=& k \cdot (k-x_1) \\ & x_1 &=& k^2 -k \cdot x_1 \\ & x_1 +k \cdot x_1 &=& k^2 \\ & x_1(1 +k ) &=& k^2 \\ & \mathbf{x_1} & \mathbf{=} & \mathbf{ \frac{k^2}{1 +k} }\\ \\ \hline \\ (1) &\frac{x_1}{x_2} &=& k \\ & x_2 &=& \frac{x_1}{k} \\ & x_2 &=& \frac{\frac{k^2}{1 +k}}{k} \\ & \mathbf{x_2} & \mathbf{=} & \mathbf{ \frac{k}{1 +k} } \\ \\ \hline \end{array} }$$

$$\small{ \begin{array}{rcll} (x-x_1)(x-x_2) &=& 0 \\ (x - \frac{k^2}{ 1 + k } )(x - \frac{k}{ 1 + k } ) &=& 0 \\ x^2-x\cdot( \frac{k}{ 1+k } + \frac{k^2}{ 1+k } ) + \frac{k^3}{ (1+k)^2 } &=& 0 \\ x^2-x\cdot[ \frac{k}{ 1+k }( 1+k ) ] + \frac{k^3}{ (1+k)^2 } &=& 0 \\ x^2-x\cdot k + \frac{k^3}{ (1+k)^2 } &=& 0 \qquad | \qquad \cdot(1+k)^2 \\ \underbrace{(1+k)^2 }_{=a}\cdot x^2 \underbrace{- k \cdot (1+k)^2 }_{=b}\cdot x + \underbrace{k^3}_{=c} &=& 0 \\ \\ \hline \\ \end{array} }$$

Example 1:

$$\begin{array}{rcll} a=(1+k)^2 \qquad b = -k \cdot (1+k)^2 \qquad c = k^3 \\ \end{array}\\ \begin{array}{rcll} \\ k & = & 1 \\ a & = & (1+1)^2 = 4 \\ b & = & -1\cdot (1+1)^2 = -4\\ c & = & 1^3 = 1\\\\ 4x^2-4x+1 &=& 0 \\ ax^2+bx+c &=& 0 \\ x_{1,2} &=& {-b \pm \sqrt{b^2-4ac} \over 2a}\\ x_{1,2} &=& {4 \pm \sqrt{(-4)^2-4\cdot 4\cdot 1} \over 2\cdot 4} \\ x_{1,2} &=& {4 \pm \sqrt{0} \over 8 } \\ x_{1,2} &=& \frac{4}{8} \\ x_{1,2} &=& \frac{1}{2} \\ x_1 &=& \frac{1}{2} \text{ or } x_1 &=& \frac{1}{2} \\\\ x_1+x_2 &=& \frac{1}{2}+\frac{1}{2} = 1 \\ \frac{x_1}{x_2} &=& \frac{\frac{1}{2}}{\frac{1}{2}} = 1 \end{array}$$

Example 2:

$$\begin{array}{rcll} a=(1+k)^2 \qquad b = -k \cdot (1+k)^2 \qquad c = k^3 \\ \end{array}\\ \begin{array}{rcll} \\ k & = & 2 \\ a & = & (1+2)^2 = 9 \\ b & = & -2\cdot (1+2)^2 = -18\\ c & = & 2^3 = 8\\\\ 9x^2-18x+8 &=& 0 \\ ax^2+bx+c &=& 0 \\ x_{1,2} &=& {-b \pm \sqrt{b^2-4ac} \over 2a}\\ x_{1,2} &=& {18 \pm \sqrt{(-18)^2-4\cdot 9\cdot 8} \over 2\cdot 9} \\ x_{1,2} &=& {18 \pm \sqrt{324-288} \over 18 } \\ x_{1,2} &=& {18 \pm \sqrt{36} \over 18 } \\ x_{1,2} &=& {18 \pm 6 \over 18 } \\ x_1 = \frac{18+6}{18} &\text{ or }& x_1 = \frac{18-6}{18} \\ x_1 = \frac{24}{18} &\text{ or }& x_1 = \frac{12}{18} \\\\ x_1 = \frac{4}{3} &\text{ or }& x_1 = \frac{2}{3} \\\\ x_1+x_2 &=& \frac{4}{3}+\frac{2}{3} = \frac{6}{3} = 2 \\ \frac{x_1}{x_2} &=& \frac{\frac{4}{3}}{\frac{2}{3}} = \frac{4}{2} = 2 \end{array}$$

heureka  Dec 14, 2015
Sort:

#1
+5

If $$\displaystyle x_{1}+x_{2}=x_{1}/x_{2},$$

then, solving for  $$x_{1}$$ ,

$$\displaystyle x_{1}=\frac{x^{2}_{2}}{(1-x_{2})}$$.

Now choose a value for x2, anything other than 1, and calculate the corresponding value of x1.

For example x2 = 2 gets you x1 = -4, and the quadratic

$$\displaystyle (x-2)(x+4)=x^{2}+2x-8=0.$$

There's an infinite number of possibilities.

Guest Dec 14, 2015
#2
+18827
+10

ax^2 +bx +c has 2 solutions, x1 and x2  x1=(-b+√Δ)/2a and x2=(−b−√Δ)2a. Is it possible that x1 + x2 = x1/x2? YES

$$\small{ \begin{array}{lrcll} (1) & x_1+x_2 &=& k & \qquad \rightarrow \qquad x_2 = k-x_1\\ (2) & \frac{x_1}{x_2} &=& k & \qquad \rightarrow \qquad x_1 = k \cdot x_2 \qquad \rightarrow \qquad x_1 = k \cdot (k-x_1)\\ \\ \hline \\ (2) & x_1 &=& k \cdot (k-x_1) \\ & x_1 &=& k^2 -k \cdot x_1 \\ & x_1 +k \cdot x_1 &=& k^2 \\ & x_1(1 +k ) &=& k^2 \\ & \mathbf{x_1} & \mathbf{=} & \mathbf{ \frac{k^2}{1 +k} }\\ \\ \hline \\ (1) &\frac{x_1}{x_2} &=& k \\ & x_2 &=& \frac{x_1}{k} \\ & x_2 &=& \frac{\frac{k^2}{1 +k}}{k} \\ & \mathbf{x_2} & \mathbf{=} & \mathbf{ \frac{k}{1 +k} } \\ \\ \hline \end{array} }$$

$$\small{ \begin{array}{rcll} (x-x_1)(x-x_2) &=& 0 \\ (x - \frac{k^2}{ 1 + k } )(x - \frac{k}{ 1 + k } ) &=& 0 \\ x^2-x\cdot( \frac{k}{ 1+k } + \frac{k^2}{ 1+k } ) + \frac{k^3}{ (1+k)^2 } &=& 0 \\ x^2-x\cdot[ \frac{k}{ 1+k }( 1+k ) ] + \frac{k^3}{ (1+k)^2 } &=& 0 \\ x^2-x\cdot k + \frac{k^3}{ (1+k)^2 } &=& 0 \qquad | \qquad \cdot(1+k)^2 \\ \underbrace{(1+k)^2 }_{=a}\cdot x^2 \underbrace{- k \cdot (1+k)^2 }_{=b}\cdot x + \underbrace{k^3}_{=c} &=& 0 \\ \\ \hline \\ \end{array} }$$

Example 1:

$$\begin{array}{rcll} a=(1+k)^2 \qquad b = -k \cdot (1+k)^2 \qquad c = k^3 \\ \end{array}\\ \begin{array}{rcll} \\ k & = & 1 \\ a & = & (1+1)^2 = 4 \\ b & = & -1\cdot (1+1)^2 = -4\\ c & = & 1^3 = 1\\\\ 4x^2-4x+1 &=& 0 \\ ax^2+bx+c &=& 0 \\ x_{1,2} &=& {-b \pm \sqrt{b^2-4ac} \over 2a}\\ x_{1,2} &=& {4 \pm \sqrt{(-4)^2-4\cdot 4\cdot 1} \over 2\cdot 4} \\ x_{1,2} &=& {4 \pm \sqrt{0} \over 8 } \\ x_{1,2} &=& \frac{4}{8} \\ x_{1,2} &=& \frac{1}{2} \\ x_1 &=& \frac{1}{2} \text{ or } x_1 &=& \frac{1}{2} \\\\ x_1+x_2 &=& \frac{1}{2}+\frac{1}{2} = 1 \\ \frac{x_1}{x_2} &=& \frac{\frac{1}{2}}{\frac{1}{2}} = 1 \end{array}$$

Example 2:

$$\begin{array}{rcll} a=(1+k)^2 \qquad b = -k \cdot (1+k)^2 \qquad c = k^3 \\ \end{array}\\ \begin{array}{rcll} \\ k & = & 2 \\ a & = & (1+2)^2 = 9 \\ b & = & -2\cdot (1+2)^2 = -18\\ c & = & 2^3 = 8\\\\ 9x^2-18x+8 &=& 0 \\ ax^2+bx+c &=& 0 \\ x_{1,2} &=& {-b \pm \sqrt{b^2-4ac} \over 2a}\\ x_{1,2} &=& {18 \pm \sqrt{(-18)^2-4\cdot 9\cdot 8} \over 2\cdot 9} \\ x_{1,2} &=& {18 \pm \sqrt{324-288} \over 18 } \\ x_{1,2} &=& {18 \pm \sqrt{36} \over 18 } \\ x_{1,2} &=& {18 \pm 6 \over 18 } \\ x_1 = \frac{18+6}{18} &\text{ or }& x_1 = \frac{18-6}{18} \\ x_1 = \frac{24}{18} &\text{ or }& x_1 = \frac{12}{18} \\\\ x_1 = \frac{4}{3} &\text{ or }& x_1 = \frac{2}{3} \\\\ x_1+x_2 &=& \frac{4}{3}+\frac{2}{3} = \frac{6}{3} = 2 \\ \frac{x_1}{x_2} &=& \frac{\frac{4}{3}}{\frac{2}{3}} = \frac{4}{2} = 2 \end{array}$$

heureka  Dec 14, 2015
#3
+18827
+10

ax^2 +bx +c has 2 solutions, x1 and x2  x1=(-b+√Δ)/2a and x2=(−b−√Δ)2a. Is it possible that x1 + x2 = x1/x2? YES

New edit, without mistake:

$$\small{ \begin{array}{lrcll} (1) & x_1+x_2 &=& k & \qquad \rightarrow \qquad x_2 = k-x_1\\ (2) & \frac{x_1}{x_2} &=& k & \qquad \rightarrow \qquad x_1 = k \cdot x_2 \qquad \rightarrow \qquad x_1 = k \cdot (k-x_1)\\ \\ \hline \\ (2) & x_1 &=& k \cdot (k-x_1) \\ & x_1 &=& k^2 -k \cdot x_1 \\ & x_1 +k \cdot x_1 &=& k^2 \\ & x_1(1 +k ) &=& k^2 \\ & \mathbf{x_1} & \mathbf{=} & \mathbf{ \frac{k^2}{1 +k} }\\ \\ \hline \\ (1) &\frac{x_1}{x_2} &=& k \\ & x_2 &=& \frac{x_1}{k} \\ & x_2 &=& \frac{\frac{k^2}{1 +k}}{k} \\ & \mathbf{x_2} & \mathbf{=} & \mathbf{ \frac{k}{1 +k} } \\ \\ \hline \end{array} }\\ \small{ \begin{array}{rcll} (x-x_1)(x-x_2) &=& 0 \\ (x - \frac{k^2}{ 1 + k } )(x - \frac{k}{ 1 + k } ) &=& 0 \\ x^2-x\cdot( \frac{k}{ 1+k } + \frac{k^2}{ 1+k } ) + \frac{k^3}{ (1+k)^2 } &=& 0 \\ x^2-x\cdot[ \frac{k}{ 1+k }( 1+k ) ] + \frac{k^3}{ (1+k)^2 } &=& 0 \\ x^2-x\cdot k + \frac{k^3}{ (1+k)^2 } &=& 0 \qquad | \qquad \cdot(1+k)^2 \\ \underbrace{(1+k)^2 }_{=a}\cdot x^2 \underbrace{- k \cdot (1+k)^2 }_{=b}\cdot x + \underbrace{k^3}_{=c} &=& 0 \\ \\ \hline \\ \end{array} }$$

Example 1:

$$\begin{array}{rcll} a=(1+k)^2 \qquad b = -k \cdot (1+k)^2 \qquad c = k^3 \\ \end{array}\\ \begin{array}{rcll} \\ k & = & 1 \\ a & = & (1+1)^2 = 4 \\ b & = & -1\cdot (1+1)^2 = -4\\ c & = & 1^3 = 1\\\\ 4x^2-4x+1 &=& 0 \\ ax^2+bx+c &=& 0 \\ x_{1,2} &=& {-b \pm \sqrt{b^2-4ac} \over 2a}\\ x_{1,2} &=& {4 \pm \sqrt{(-4)^2-4\cdot 4\cdot 1} \over 2\cdot 4} \\ x_{1,2} &=& {4 \pm \sqrt{0} \over 8 } \\ x_{1,2} &=& \frac{4}{8} \\ x_{1,2} &=& \frac{1}{2} \\ x_1 = \frac{1}{2} &\text{ or }& x_2 = \frac{1}{2} \\\\ x_1+x_2 &=& \frac{1}{2}+\frac{1}{2} = 1 \\ \frac{x_1}{x_2} &=& \frac{\frac{1}{2}}{\frac{1}{2}} = 1 \end{array}$$

Example 2:

$$\begin{array}{rcll} a=(1+k)^2 \qquad b = -k \cdot (1+k)^2 \qquad c = k^3 \\ \end{array}\\ \begin{array}{rcll} \\ k & = & 2 \\ a & = & (1+2)^2 = 9 \\ b & = & -2\cdot (1+2)^2 = -18\\ c & = & 2^3 = 8\\\\ 9x^2-18x+8 &=& 0 \\ ax^2+bx+c &=& 0 \\ x_{1,2} &=& {-b \pm \sqrt{b^2-4ac} \over 2a}\\ x_{1,2} &=& {18 \pm \sqrt{(-18)^2-4\cdot 9\cdot 8} \over 2\cdot 9} \\ x_{1,2} &=& {18 \pm \sqrt{324-288} \over 18 } \\ x_{1,2} &=& {18 \pm \sqrt{36} \over 18 } \\ x_{1,2} &=& {18 \pm 6 \over 18 } \\ x_1 = \frac{18+6}{18} &\text{ or }& x_2 = \frac{18-6}{18} \\ x_1 = \frac{24}{18} &\text{ or }& x_2 = \frac{12}{18} \\\\ x_1 = \frac{4}{3} &\text{ or }& x_2 = \frac{2}{3} \\\\ x_1+x_2 &=& \frac{4}{3}+\frac{2}{3} = \frac{6}{3} = 2 \\ \frac{x_1}{x_2} &=& \frac{\frac{4}{3}}{\frac{2}{3}} = \frac{4}{2} = 2 \end{array}$$

heureka  Dec 14, 2015

### 16 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details